Liquid crystal based phased array antenna with improved beam scanning capability. Issue 6 (1st March 2014) - Karabey, O.H.; Mehmood, A.; Ayluctarhan, M.; Braun, H.; Letz, M.; Jakoby, R.
Abstract : A phased array antenna is presented, including a 1‐by‐4 dielectric resonator antenna (DRA) array, liquid crystal (LC) based phase shifters, RF‐feeding and biasing networks. The dielectric resonators are used as waveguide radiating elements. The RF signal coupled between the phase shifters and DRAs are guided and then radiated from the top face of the DRAs. This reduces the effects of the surface waves since the radiation is away from the ground plane. Hence, the gain losses at wide scan angles are reduced, enlarging the antenna's beam scan angle, compared to that of a conventional microstrip patch antenna array. The LC phase shifters are realised in inverted microstrip line topology, with a phase shifter figure‐of‐merit of 70°/dB at 10 GHz. The far‐field power patterns of the antenna were measured in an anechoic chamber for different beam directions. These results confirm that the gain losses are <1.5 for a beam scanning range of ±30° for the broadside.